2016
DOI: 10.1016/j.foodhyd.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan nanoparticles on the improvement of thermal, barrier, and mechanical properties of high- and low-methyl pectin films

Abstract: Please cite this article as: Lorevice, M.V., Otoni, C.G., Moura, M.R.d., Mattoso, L.H.C., Chitosan nanoparticles on the improvement of thermal, barrier, and mechanical properties of high-and low-methyl pectin films, Food Hydrocolloids (2015), ABSTRACT 26Non-biodegradable food packaging materials has caused serious environmental 27 problems due to their inappropriate discard. Biodegradable and renewable polymers 28 (e.g., polysaccharides), when reinforced with nanostructures, have been used to produce 29 novel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 48 publications
4
66
2
2
Order By: Relevance
“…CSNPs average size has been demonstrated to depend upon chitosan and TPP concentrations (Calvo et al., ). The values obtained here are similar to previous reports (Lorevice et al., ). Concerning surface charge, the CSNPs synthesized here presented an average zeta potential value of +30 mV.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…CSNPs average size has been demonstrated to depend upon chitosan and TPP concentrations (Calvo et al., ). The values obtained here are similar to previous reports (Lorevice et al., ). Concerning surface charge, the CSNPs synthesized here presented an average zeta potential value of +30 mV.…”
Section: Resultssupporting
confidence: 93%
“…This parameter is an indication of the stability of a colloidal system. The zeta potential obtained here is favorable for the kinetic stability of the particle aqueous suspension, since values greater than 20 mV in magnitude have been reported to lead to suitably stable systems (Lorevice et al., ). The positive net charge is related to the cationic groups of the acidic chitosan, as described previously (Rampino, Borgogna, Blasi, Bellich, & Cesàro, ).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Otoni et al noted an improvement in the physical, mechanical, barrier, and antimicrobial properties in pectin/papaya purée‐based films incorporated with essential oil nanoemulsions. Pectin films with chitosan nanoparticles also showed an improvement in their mechanical and thermal properties . Abral et al studied the changes in the properties of starch films after ultrasonic processing and showed that decreasing the size of gelatinized granules results in films with lower moisture vapor permeability, higher thermal resistance, increased the tensile strength of the film, and decreased moisture absorption.…”
Section: Introductionmentioning
confidence: 99%